Pengaruh Literasi Keuangan dan E-money terhadap Perilaku Konsumtif: Studi pada Mahasiswa Manajemen Universitas Buana Perjuangan Karawang Angakatan 2019 - Nurunnisa, Intan; Marliani, Sari; Yuliawati, July (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research was conducted to determine the influence of financial literacy (X1) and e-money (X2) on consumptive behavior (Y) in management students at Buana Perjuangan University, Karawang. The research employed a quantitative approach, utilizing multiple regression analysis for data analysis. The data processing was conducted using SPSS 24 software. The primary data source was gathered through the distribution of questionnaires to management students at Buana Usaha University, Karawang. The population chosen for this research was management students at Buana Usaha Karawang University, totaling 350 students with a sample of 186 students using the Slovin Formula as a sampling technique. The findings indicate that the variable of financial literacy has a favorable impact on consumptive behavior. Similarly, the variable of e-money also has a positive influence on consumptive behavior. Furthermore, when considering both financial literacy and e-money together, they collectively have an impact on consumptive behavior. The consumer behavior variable is influenced by the financial literacy and e-money variables by 50%.